1993
DOI: 10.1016/0014-5793(93)81399-k
|View full text |Cite
|
Sign up to set email alerts
|

Amyloidogenicity of rodent and human βA4 sequences

Abstract: Previously we have shown that aggregation of the C-terminal 100 residues (A4CT) of the DA4 amyloid protein precursor (APP) and also of /?A4 itself depends on the presence of metal-catalyzed oxidation systems [T. Dyrks et al. (1988) EMBO J. 7, 949-9571. We showed that aggregation of the amyloidogenic peptides induced by radical generation systems requires amino acid oxidation and protein cross-linking.Here we report that aggregation of A4CT and PA4 induced by radical generation systems involves oxidation of hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
115
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 175 publications
(123 citation statements)
references
References 30 publications
8
115
0
Order By: Relevance
“…Several reports have revealed that exogenous AR causes neuronal degeneration in primary cultured neurons (Yankner et [G1u22]AR1-28 peptide solution. Dyrks et al (1993) have shown that the aggregation of A/3 and the C-terminal amyloidogenic APP fragments depend on oxidation of His, Tyr and Met residues, and that the addition of radical scavengers prevents the aggregation process induced by metal-catalyzed oxidation systems (Dyrks et al 1992). The report that the iron homeostasis is disrupted in Alzheimer's disease brains (Kawamata et al 1993) may also supports the involvement of metal-catalyzed radical reactions in the aggregation process of AR (Dyrks et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have revealed that exogenous AR causes neuronal degeneration in primary cultured neurons (Yankner et [G1u22]AR1-28 peptide solution. Dyrks et al (1993) have shown that the aggregation of A/3 and the C-terminal amyloidogenic APP fragments depend on oxidation of His, Tyr and Met residues, and that the addition of radical scavengers prevents the aggregation process induced by metal-catalyzed oxidation systems (Dyrks et al 1992). The report that the iron homeostasis is disrupted in Alzheimer's disease brains (Kawamata et al 1993) may also supports the involvement of metal-catalyzed radical reactions in the aggregation process of AR (Dyrks et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The exact amyloidogeni¢ mechanism by which pA4 is cleaved from APP and deposited in AD remains unknown, although our earlier [1] and reins studies [15] suggest that th¢ initial step of the abnormal processing of full-length APP in Alzheimer's disease may occur at the NH,.terminus of the 3A4 sequence and generate a COOH-terminal fragment of 100 residues (A4CT), which includes the amyloid pA4 sequence, and the transmembrane and cytoplasmic domains of all known transmembrane APP forms.…”
Section: L Introductionmentioning
confidence: 93%
“…In particular, the accumulation of aggregated amyloid β-protein in diseased brains as neurofibrillary tangles can occur through oxidation [270], and mitochondrial dysfunction has been envisaged as a radical source [271].…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%